Three-dimensional fine crust-mantle structure imaging and structural characteristics of Bohai Sea - Yong Ma; Lei Gao; Demiao Dong (Scientific Reports, 2024)
Abstract This study used the consistency-constrained double-difference tomography method to invert 3D fine structure models of Vp, Vs, Vp/Vs at depths above 60 km, and precise relocation parameters of earthquakes in the Bohai Sea. According to the results, the velocity structures of P-wave and S-wave in the Bohai Sea area were highly similar and demonstrated noticeable lateral non-uniformity. The crust beneath the Tanlu Fault displayed a clear stratification structure, with a continuous velocity transition in the middle of the crust. The intricate crustal structure beneath the Zhangpeng Fault displayed high-velocity bodies in the crust and low-velocity anomalous zones connected to the top of the mantle in the lower section of the crust. The structural pattern in the deep crust of the Bohai Sea controls the occurrence characteristics of the Zhangpeng Fault and the Tanlu Fault. The earthquakes in the Bohai Sea area were concentrated mainly in the southern part near the Zhangpeng Fault. There is a good correspondence between the relocated earthquakes and velocity structure. There are many significant differences in crustal structure between the north and south of the Bohai Strait, and there are obvious velocity anomalies in the middle and upper crust. The distribution shape of high Vp/Vs value indicates that mantle material migration has occurred at the bottom of the crust. This paper provided important reference for further research on the relationship between deep tectonic features and tectonic activity in the North China Craton.